Model for distribution of warehouses in the commercial network in optimising transportation of goods - Baublys, Adolfas (Transport, 2008)
A model for distribution of warehouses in the commercial network in optimising transportation of goods has been established. The target function in the model includes: fixed prices for construction of big and small warehouses; variable prices for transportation of raw materials and goods between warehouses and commercial points. The algorithm was created for optimisation of local roads network between commercial points. As substantiated, if density of distribution of target function values in the zone of extreme is fairly high, the independent random search is sufficiently effective even when comparing it with regular methods.First published online: 27 Oct 2010